2011
DOI: 10.1590/s0103-64402011000300008
|View full text |Cite
|
Sign up to set email alerts
|

Syndecan-1 (CD138) and Ki-67 expression in odontogenic cystic lesions

Abstract: The aim of this study was to assess the immunohistochemical expression of syndecan-1 (CD138) and Ki-67 in radicular cysts (RC), dentigerous cysts (DC) and keratocystic odontogenic tumors (KOT). Thirty-five RC, 22 DC and 17 KOT were used in the study and immunohistochemical reactions using anti-syndecan-1 and anti-Ki-67 antibodies were performed by the streptavidin-biotin-peroxidase method. Fisher's exact test and Spearman's correlation coefficient were used for statistical analysis of data. Among the studied l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
21
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 20 publications
(36 reference statements)
8
21
1
Order By: Relevance
“…In our series, all ameloblastomas were unicystic. In the study of Nadalin et al (29), CD138 expression was detected in all epithelial layers of KCOTs, RCs and DCs. Our results were similar to the findings of previous studies, but we also observed CD138 expression in the stromal cells.…”
Section: Some Authors Suggested That Loss Of E-cadherin Expression Inmentioning
confidence: 87%
See 1 more Smart Citation
“…In our series, all ameloblastomas were unicystic. In the study of Nadalin et al (29), CD138 expression was detected in all epithelial layers of KCOTs, RCs and DCs. Our results were similar to the findings of previous studies, but we also observed CD138 expression in the stromal cells.…”
Section: Some Authors Suggested That Loss Of E-cadherin Expression Inmentioning
confidence: 87%
“…Although there are several studies related to role of these proteins in odontogenic lesions in English literature (8,9,18,24,(27)(28)(29), no comparative and comprehensive study, in which the expression of these proteins or adhesion molecules in odontogenic cystic lesions have been evaluated, to our knowledge. Therefore, we aim to evaluate the immunohistochemical expressions of CD138 (syndecan-1), CD38, E-cadherin and survivin in these cystic odontogenic lesions and investigate the potential implications of their expressions among these lesions.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have focused on the etiopathogenesis of chronic periapical lesions, odontogenic cysts and tumors, using immunohistochemistry to investigate the role of cytokines, growth factors, cellular differentiation factors, tumor suppressor genes and oncogenes in the initiation, development, and progression of these lesions (4,6,(12)(13)(14)(15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…Since KOT had been classified as an odontogenic cyst, several authors have compared cell proliferation between KOT and odontogenic cysts (8,12,13). Although several authors have assessed cell proliferation and apoptosis in the odontogenic epithelium in AM and in the epithelial lining in KOT (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22), few studies have compared cell proliferation between these tumors (7,8,11) and no previous study has simultaneously evaluated cell proliferation and apoptotic indexes in AM and KOT, comparing both lesions. Therefore, this is the first study assessing comparatively cell proliferation and apoptosis indexes in AM and KOT, although tissue cell population is controlled by a balance among these processes.…”
Section: Discussionmentioning
confidence: 99%